Editorial: potassium‐competitive acid blockers for acid‐related diseases—tegoprazan, a new kid on the block. Issue 8 (7th October 2019) - Scarpignato, Carmelo; Hunt, Richard H.
Abstract : LINKED CONTENT This article is linked to Han et al paper. To view this article, visithttps://doi.org/10.1111/apt.15438 .